Weak Correlation between the Polyanion Environment and Ionic Conductivity in Amorphous Li-P-S Superionic Conductors - Lee, Byungju; Jun, KyuJung; Ouyang, Bin; Ceder, Gerbrand (American Chemical Society, 2023)
Amorphous Li-P-S materials have been widely used as solidstate electrolytes for all-solid-state batteries because of their high ionic conductivity (10-4 to 10-3 S cm-1) as well as good synthetic accessibility and processability. Despite the potential of these materials, their amorphous structures have made it challenging to quantify the relation between the structure and conductivity. In this paper, we use ab initio molecular dynamics simulations to investigate the role of the local structure and density in determining the conductivity of amorphous Li-P-S structures with different polyanion units. We observe similar rates for Li-ion hopping regardless of the local P-S polyanion environment in these amorphous materials, indicating that the path connectivity at a larger length scale may be controlling the overall Li conductivity. This finding will serve as an important guideline in the continued development of amorphous solid electrolytes for advanced all-solid-state batteries.